A MINI REVIEW ON THE NUTRITIONAL COMPOSITIONS AND PHARMACOLOGICAL PROPERTIES OF Litsea garciae - Zunika, Amit; Zinyin, Ling (The Malaysian Society of Applied Biology, 2021)
Litsea garciae is an underutilized plant found in certain parts of South East Asia. The plant part has been traditionally used to treat, among others, skin infections, boil, rectal bleeding, muscular pain, and sprains. Besides its medicinal properties, its seasonal fruit is consumed for its avocado-like flavor. This article aims to provide information on what is known so far about the nutritional composition and pharmacological properties of Litsea garciae.